Corporate social responsibility and behavioral intentions in an emerging market: The mediating roles of green brand image and green trust - Bang Nguyen-Viet; Cong Thanh Tran; Hoa Thi Kim Ngo (Cleaner and Responsible Consumption, 2024)
This study is driven by the absence of thorough investigations into the behavioral intentions of organizational consumers in the B2B market for paint and coatings, particularly within the industrial and marine coatings sector in Vietnam. Employing the stimulus–organism–response model, we tested the relationship between corporate social responsibility (CSR), green brand image (GBI), green trust (GT), and behavioral intentions (word-of-mouth intention, willingness to pay, and purchase intention) in the Vietnamese industrial and marine coatings industry. We also examined how GBI and GT mediate the relationship between CSR and behavioral intentions. Structural equation modeling was used to test the structural and measurement models and hypothetical relationships. The sample comprised 332 responses from stakeholders in the Vietnamese coating industry. Evidently, GT and CSR positively influenced word-of-mouth, willingness-to-pay, and green purchase intentions, with trust and commitment to sustainability being important drivers. While GBI positively influences purchase intention and willingness-to-pay, it has a weak effect on word-of-mouth intention, indicating that additional strategies are needed to stimulate word of mouth. Further, GT mediates the relationship between green purchase intentions and GBI, as well as between CSR and green purchase intentions. The outcomes highlight the value of incorporating CSR, GT, and GBI into the business strategies of Vietnamese industrial and marine coating companies. We discuss several theoretical and managerial implications, and the importance of studying the influence of GT, CSR, and GBI on consumers’ behavioral intentions across various cultural contexts.